Airbag Phone Case / Muhamad Akmal Abdullah Zawawi - Abdullah Zawawi, Muhamad Akmal (2020)
Our company developed new product which is airbag phone case. The purpose to create this product is to create a casing that can protect the front and the back of the phone completely, especially on the front of the phone because the screen is easily cracked. We also want to introduce this idea into the market to improve the quality of the phone case that worth the price. This product could help people to save hundreds of dollars they would otherwise end up spending on phone repairs or new devices since people tend to drop and break their smartphones all the time. For a baseline level of protection, we will use a case made of a shock-absorbent material such as silicone or rubber that covers the phone’s vulnerable corners.